Fruitless isoforms and target genes specify the sexually dimorphic nervous system underlying Drosophila reproductive behavior. - Nojima, T; Neville, M; Goodwin, S (Taylor and Francis, 2014)
Courtship is pivotal to successful reproduction throughout the animal kingdom. Sexual differences in the nervous system are thought to underlie courtship behavior. Male courtship behavior in Drosophila is in large part regulated by the gene fruitless (fru). fru has been reported to encode at least three putative BTB-zinc-finger transcription factors predicted to have different DNA-binding specificities. Although a large number of previous studies have demonstrated that fru plays essential roles in male courtship behavior, we know little about the function of Fru isoforms at the molecular level. Our recent study revealed that male-specific Fru isoforms are expressed in highly overlapping subsets of neurons in the male brain and ventral nerve cord. Fru isoforms play both distinct and redundant roles in male courtship behavior. Importantly, we have identified for the first time, by means of the DamID technique, direct Fru transcriptional target genes. Fru target genes overwhelmingly represent genes previously reported to be involved in the nervous system development, such as CadN, lola and pdm2. Our study provides important insight into how the sexually dimorphic neural circuits underlying reproductive behavior are established.